Self-humiliating discourse in Los cortejos del Diablo - Ferrer, Gabriel Alberto (Íkala, Revista de Lenguaje y Cultura, 1998)
In this article, the author analyzes Germán Espinosa's novel, «Los Cortejos del Diablo» within the framework of sociocritcism. He relates discourse formations such as self-humiliation, confession and gossip during the period of Inquisition and present- day society.